Factors associated with cesarean delivery in public and private hospitals in a city of northeastern Brazil: a cross-sectional study - Vieira, Graciete Oliveira (BMC Pregnancy Childbirth, 2015)
BACKGROUND: To evaluate the prevalence and factors associated with cesarean delivery according to whether care was provided in public or private hospitals in Brazil. METHODS: This was a cross-sectional study based on a cohort of live births between April 2004 and March 2005. A total of 1,344 mother-child pairs were followed up during the first month of life. The variables analyzed were the socioeconomic and demographic characteristics of the mother and newborn, as well as the healthcare provided during pregnancy and childbirth. Hierarchical analysis was carried out for both prediction models, i.e. healthcare provision either within the Brazilian National Health System (public service) or within the private network. Prevalence and association measurement calculations were carried out. Values were considered significant when pless than or equal to 5.0 %. RESULTS: A total of 1,019 (75,8 %) gave birth in public hospital. The prevalences of cesarean delivery were 29.9 % and 86.2 % in the public and private sectors, respectively. Through hierarchical logistic regression, the risk factors for cesarean delivery presented in the public hospital were maternal age greater than or equal to 20 years (p = 0.003), primiparity (p = 0.004), twinning (p = 0.039), prenatal care provided in the private network (p = 0.004), delivery in hospitals providing high complexity medical care (p = 0.000) and prenatal care with greater than or equal to 6 consultations (p = 0.035). In the private sector, no association was observed between the variables studied and cesarean delivery. CONCLUSIONS: The cesarean delivery rates were high in both sectors, although in the private network the rate was almost triple that of the public service. The absence of determinant factors of birth in the private sector drew attention. In planning measures against the growing cesarean rates, it is necessary to take into consideration the environmental determinants as primiparity, twinning and greater maternal age, frequent indications of primary cesarean delivery, as well as to implement actions that might improve the quality of prenatal and delivery care.